Hydrodynamic loadings on a horizontal axis tidal turbine prototype. (May 2017) - Ouro, Pablo; Harrold, Magnus; Stoesser, Thorsten; Bromley, Peter
Abstract: Until recently tidal stream turbine design has been carried out mainly by experimental prototype testing aiming at maximum turbine efficiency. The harsh and highly turbulent environments in which tidal stream turbines operate in poses a design challenge mainly with regards to survivability of the turbine owing to the fact that tidal turbines are exposed to significant intermittent hydrodynamic loads. Credible numerical models can be used as a complement to experiments during the design process of tidal stream turbines. They can provide insights into the hydrodynamics, predict tidal turbine performance and clarify their fluid–structure interaction as well as quantify the hydrodynamic loadings on the rotor. The latter can lead to design enhancements aiming at increased robustness and survivability of the turbine. Physical experiments and complementary large-eddy simulations of flow around a horizontal axis tidal turbine rotor are presented. The goal is to provide details of the hydrodynamics around the rotor, the performance of the turbine and acting hydrodynamic forces on the rotor blades. The simulation results are first compared with the experimental and good agreement between measured and simulated coefficients of power are obtained. Acting bending and torsional moment coefficients on the blade-hub junction are computed for idealised flow conditions. Finally, realistic environmental turbulence is added to the inflow and its impact on the turbine's performance, hydrodynamics and rotor loadings is quantified.